Analysis of students error in mathematical problem solving based on Newman’s error analysis - H N Fitriani; T Turmudi; S Prabawanto (Pascasarjana Universitas Pendidikan Indonesia, 2018)
After conducting literature studies, the researchers found that more studies on problem solving focused on the application of learning methods and the development of teaching materials to improve students problem-solving ability rather than identification and discovery of student errors. This study aims to describe students error according to Newman's Error Analysis in solving derivative of algebraic function problem. This research used a qualitative approach with case study design and purposive sampling technique. Data were collected through problem-solving test on derivative of algebraic function and interview of senior high school students grade 11 in Bandung. The results of this study showed that students did five types of errors in solving the problem of derivative of algebraic function that were comprehension error, transformation error, process skill error, encoding error and careless. Analysis of student error was expected to help to reflect on solving mathematical problems and became a reference for teachers in choosing strategy, model or learning media to reduce errors made by students.